Translation and cross-cultural adaptation of the “Vanderbilt Pediatric Dizziness Handicap Inventory for Patient Caregivers" questionnaire to Portugal for pediatric vertigo evaluation - Nascimento, Joana (2023)
Vestibular disorders in childhood may lead to avoidance behaviours, with associated adverse effects, and thus rapid diagnosis is important. This study aims to translate to European Portuguese and culturally adapt the "Vanderbilt Pediatric Dizziness Handicap Inventory for Patient caregivers" (DHI-PC) questionnaire to Portugal. The methodological sequence used was based on the steps recommended in the international literature. Three focus groups were conducted to evaluate the preservation of the construct and the correct understanding of sentences and expressions. The team responsible for the adaptation reached consensus taking into account the changes discussed in the focus groups, with the purpose of achieving semantic, idiomatic, experimental, and conceptual equivalence, which would ensure an accurate translation and an adequate cultural adaptation. For its use in clinical practice, validation of the instrument will be carried out in a second phase.